Power density dynamics in a nuclear reactor with an extended in-core pulse-periodic neutron source based on a magnetic trap; Nuclear Energy and Technology; Vol. 6, № 3 - Shamanin I. V. Igor Vladimirovich; Bedenko S. V. Sergey Vladimirovich; Shmakov V. M. Vladimir Mikhaylovich; Modestov D. G. Dmitry Gennadjevich; Lutsik I. O. Igor Olegovich (2020, 2020)
Заглавие с экрана